Immune Responses Elevation by Intranasal Administration of Chitosan Microparticles Adjuvanted Poly-Epitope against Streptococcus pneumoniae in BALB/c Mice: Immune responses elevation against S. pneumoniae mice - Sadeghi, Sahar; Bandehpour, Mojgan; Haji Molla Hoseini, Mostafa; Kazemi, Bahram (Novelty in Biomedicine, 2022)
Background: Designing inhaled vaccine formulations against respiratory pathogens like Streptococcus pneumoniae (S. pneumoniae) lead to more effective mucosal and local immunity in the upper respiratory tract. Choosing chitosan (the chitin de-acetylated derivative) as a biocompatible, biodegradable, and non-toxic biopolymer and a suitable mucosal adjuvant can help to stimulate both systemic cellular and humoral immunity, as well as local protection, is valuable. The purpose of this study is the determination the ability of the designed pneumococcal immunogenic polytope to evoke a bactericidal response when adjuvanted with chitosan microparticles. Materials and Methods: We chose virulence proteins from S. pneumoniae (Pneumolysin, Neuraminidase, ZinkMetalloproteinase, Hydrolase) and designed a new multi-epitope construct by linking their individual predicted T and B cell epitopes. Intranasal immunization with PNEU protein and chitosan microparticle administered in BALB/c mice. Results: Our formulation showed enhanced systemic IgG-2a, IgA, and mucosal IgA antibody concentrations, revealing significant humoral responses to the polytope. The polytope increases the number of IFN-γ- producing cells in the re-stimulation of splenocytes in the culture medium and a rise in the concentrations of IL-6, IL-17, and TNF-α along with the regulatory responses of IL-10 presented the capacity of the formulation to provoke immune responses. The bactericidal test ultimately confirmed the high efficacy of the vaccine in inhibiting the bacteria. Conclusion: Immunological responses were significantly induced after intranasal administration of the S. pneumoniae computational predicted polytope accompanied by chitosan microparticles as a potent mucosal adjuvant. Bactericidal assay confirmed effective immune responses in S. pneumoniae inhibition.